Development of a checklist for neonatal perioperative care in cardiac surgery - Gobo de Oliveira, Mariele [UNESP]; Aparecida de Jesus Castro Santos, Mariana [UNESP]; Carvalho, Nyara Coelho [UNESP]; Barboza, Ana Lúcia Monaro [UNESP]; Fausto de Morais, José; Meneguin, Silmara [UNESP] (Acta Paulista de Enfermagem, 2024)
Objective: To build and validate checklist content for neonatal perioperative nursing care in cardiac surgery. Methods: This is methodological research, developed from October 2020 to September 2021, in two sequential stages: checklist item construction based on an integrative literature review and content validity by seven experts in neonatology, selected from a search in resumes. For analysis, the Content Validity Index was used, considering values ≥ 0.8. Results: A checklist was created with 57 structured items for pre-, intra- and postoperative interventions in cardiac surgery, with care actions designated according to the legal competence of nursing professional (technician and nurse) categories. In the validity process, 24 items were modified and four were excluded. The minimum level of agreement among experts for the items was 0.86, except for one item (0.75). Conclusion: The checklist achieved content validity with a satisfactory standard for use in the perioperative period of cardiac surgery. Resumo Objetivo: Construir e validar conteúdo de checklist para assistência de enfermagem perioperatória neonatal em cirurgia cardíaca. Métodos: Pesquisa metodológica, desenvolvida no período de outubro de 2020 a setembro de 2021, em duas etapas sequenciais: construção dos itens do checklist a partir de revisão integrativa da literatura e validação de conteúdo por sete especialistas em neonatologia, selecionados a partir de busca curricular. Para análise, utilizou-se o índice de validade de conteúdo, considerando valores ≥ 0,8. Resultados: Construiu-se um checklist com 57 itens estruturado para intervenções no pré, intra e pós-operatório de cirurgia cardíaca, com ações assistenciais designadas de acordo com a competência legal das categorias dos profissionais de enfermagem (técnico e enfermeiro). No processo de validação, 24 itens foram modificados e quatro excluídos. O nível de concordância mínimo entre os especialistas para os itens foi de 0,86, exceto para um item (0,75). Conclusão: O checklist alcançou validade de conteúdo com padrão satisfatório para utilização no perioperatório de cirurgia cardíaca.
Elaboración de checklist para la atención perioperatoria neonatal en cirugías cardíacas
Desenvolvimento de checklist para assistência perioperatória neonatal em cirurgia cardíaca
Keywords: Checklist; congenital; Heart defects; Intensive care units; neonatal; Neonatal nursing; Nursing care; Perioperative care; Thoracic surgery